2008
DOI: 10.1094/phyto-98-2-0159
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Fusarium graminearum Species Complex in Japan

Abstract: Members of the Fusarium graminearum species complex are important cereal pathogens worldwide and belong to one of at least nine phylogenetically distinct species. We examined 298 strains of the F. graminearum species complex collected from wheat or barley in Japan to determine the species and trichothecene chemotype. Phylogenetic analyses and species-diagnostic polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLPs) revealed the presence and differential distribution of F. graminearum se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
152
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 20 publications
6
152
1
3
Order By: Relevance
“…In Asia, temperature is frequently used to explain F. graminearum as the predominant species of FGSC in northern areas, while F. asiaticum dominates southern areas (Qu et al, 2008;Suga et al, 2008). However, our previous study did not corroborate this finding.…”
Section: Discussioncontrasting
confidence: 66%
“…In Asia, temperature is frequently used to explain F. graminearum as the predominant species of FGSC in northern areas, while F. asiaticum dominates southern areas (Qu et al, 2008;Suga et al, 2008). However, our previous study did not corroborate this finding.…”
Section: Discussioncontrasting
confidence: 66%
“…F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014). While the species within the FGSC show a significant biogeographic structure (Aoki et al 2012), substantial species diversity has been observed in South America (Scoz et al 2009;Sampietro et al 2010;Umpiérrez-Failache et al 2013), Asia (Yli-Mattila et al 2009Suga et al 2008;Zhang et al 2012), Africa (Boutigny et al 2011;O'Donnell et al 2008) and New Zealand (Monds et al 2005). Long-distance dispersal and anthropogenic activities have the potential to alter regional pathogen composition as suggested by the recent discovery of significant populations of F. asiaticum, an Asian endemic that appears to be adapted to rice agroecosystems (Lee et al 2009), on wheat in major rice production areas of Louisiana and Uruguay .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Recently, genetic species identification of the F. graminearum species complex and determination of its trichothecene chemotypes by PCR-RFLP and multiplex PCR were reported. 14) In Japan, it was demonstrated that 2 species predominate among the F. graminearum species complex (Fusarium asiaticum and Fusarium graminearum s. str.).…”
Section: Introductionmentioning
confidence: 99%
“…15) Their mycotoxin-producing profiles have been examined, and the characteristics of their geographical distributions have also been reported. 14,[16][17][18][19][20][21] Metconazole ((1RS, 5RS; 1RS, 5SR)-5-(4-chlorobenzyl)-2,2-dimethyl-1-(1H-1,2,4-triazol-1-ylmethyl) cyclopentanol), a demethylation inhibitor of the ergosterol biosynthesis pathway (DMI), was synthesized and its biological activity was found by the Kureha Corporation in 1986. 22) It was first launched as a cereal fungicide in France in 1994, and had been globally registered and was being used as a fungicide for Sensitivity of Japanese Fusarium graminearum species complex isolates to metconazole cereals, oil seed rape, turf, tree nuts, fruits and many other kinds of crops in more than 30 countries by 2009.…”
Section: Introductionmentioning
confidence: 99%